A comment on 'Expressions of dependency: green crimes and the phantasmagoria of "development" in the extreme west of Bahia, Brazil' - Durazo Herrmann, Julián (Criminological encounters, 2022)
Brief review and comment on "Expressions of dependency: green crimes and the phantasmagoria of "development" in the extreme west of Bahia, Brazil".